2012
DOI: 10.1371/journal.pone.0046945
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Calvarial Healing in Mice Lacking Toll-Like Receptor 4

Abstract: The bone and immune systems are closely interconnected. The immediate inflammatory response after fracture is known to trigger a healing cascade which plays an important role in bone repair. Toll-like receptor 4 (TLR4) is a member of a highly conserved receptor family and is a critical activator of the innate immune response after tissue injury. TLR4 signaling has been shown to regulate the systemic inflammatory response induced by exposed bone components during long-bone fracture. Here we tested the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 31 publications
1
34
1
Order By: Relevance
“…[30] In a previous study, accelerated bone healing within a calvarial defect model was observed in TLR4 -/-mice, suggesting that TLR4 signaling is detrimental to the normal healing of calvarial bone defects. [21] In contrast to our previous findings, we report here that TLR4 is required to support graft-induced bone repair using a calvarial defect model. At day7 after implantation, WT mice showed more F4/80 positive macrophage lineage cell infiltration, while macrophages were not detected in TLR4 -/-mice after bone component implantation.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…[30] In a previous study, accelerated bone healing within a calvarial defect model was observed in TLR4 -/-mice, suggesting that TLR4 signaling is detrimental to the normal healing of calvarial bone defects. [21] In contrast to our previous findings, we report here that TLR4 is required to support graft-induced bone repair using a calvarial defect model. At day7 after implantation, WT mice showed more F4/80 positive macrophage lineage cell infiltration, while macrophages were not detected in TLR4 -/-mice after bone component implantation.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been argued that the regenerative potential of bone graft is dependent upon the efficient transfer of progenitor cells to the defect site, [36,37] although donor cells typically fail to survive beyond hours to weeks. [38,39] In our previous work, [21] we used radiographic bone measurement to assess bone repair in a calvarial defect model and observed that 33.14% of the defect had regenerated by day 28 in WT mice, while the current study showed that BC and ME (matrix-enriched) groups achieved 74.80% and 66.79%, respectively (Fig.6). The CE (cellenriched) implant, in contrast, failed to stimulate bone repair beyond control values.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations